Standing on Holy Ground in the Middle Ages - Donkin, Lucy; Donkin, Lucy (Book collections on Project MUSE., 2021)
"Discusses the significance of holy ground within medieval Christianity. It encompasses the material and visual properties of the ground including pavement decoration; physical contact with the surface within and beyond religious ritual; and how this shaped the definition of sacred space and the identity of individuals and communities"